New Insights into the Modifications and Bioactivities of Indole-3-Carboxaldehyde and its Derivatives as a Potential Scaffold for Drug Design: A Mini-Review - Mukhtar, Nuhu Abdullahi; Suleiman, Mustapha; Al-Maqtari, Helmi Mohammed; Das, Kumitaa Theva; Bhat, Ajmal R.; Jamalis, Joazaizulfazli (Mini Reviews in Medicinal Chemistry, 2025)
Indole, a ubiquitous structural motif in bioactive compounds, has played a pivotal role in drug discovery. Among indole derivatives, indole-3-carboxaldehyde (I3A) has emerged as a particularly promising scaffold for the development of therapeutic agents. This review delves into the recent advancements in the chemical modification of I3A and its derivatives, highlighting their potential applications in various therapeutic areas. I3A derivatives have demonstrated a wide range of biological activities, including anti-inflammatory, anti-leishmanial, anti-cancer, anti-bacterial, anti-fungal, and anti-HIV properties. The structural modifications introduced to the I3A scaffold, such as substitutions on the indole ring (alkylation/arylation/halogenation), variations in the aldehyde group via condensation (Aldol/Claisen/Knoevenagel), and molecular hybridization with other reputable bioactive compounds like coumarins, chalcones, triazoles, and thiophenes, contribute to these activities. Beyond its therapeutic potential, I3A has also found applications as a ligand for Schiff base synthesis, a polymer, and a chromophore. This review provides a comprehensive overview of the latest research on I3A and its derivatives, focusing on the key reactions, modification pathways, reaction conditions, yields, and associated therapeutic activities. By understanding these advancements, researchers can gain valuable insights into the potential applications and future directions for I3A-based drug discovery.
Keywords: triazoles